(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: Gender dysphoria is characterized by marked incongruence between the assigned gender at birth and the experienced gender, leading to significant emotional distress affecting mental health, social interactions, and overall well-being. In Bangladesh, published data on patients with gender dysphoria remain scarce, and persistent social stigma, discrimination, and barriers to care continue to affect timely help-seeking and access to appropriate psychological support. Objectives: To determine the socio-demographic characteristics, clinical pattern, and mental health status of patients with gender dysphoria. Methods: This cross-sectional study was conducted at the Department of Endocrinology, Dhaka Medical College Hospital, from January to December 2024. Fifty patients with gender dysphoria were enrolled using purposive sampling. Participants underwent a detailed assessment, including socio-demographic characteristics, clinical pattern evaluation, and mental health status assessment using the validated Bangla version of the Depression Anxiety Stress Scale-21 (DASS-21). Data were analyzed using Statistical Package for Social Sciences (SPSS) version 27 (IBM Corp., Armonk, NY). Results: The mean age was 26.16±9.99 years, with most participants being students (48%) and single (84%). Mean age of onset of gender dysphoria was 13.56±7.38 years, while first consultation occurred at 22.36±7.98 years. Among participants, 66% assigned male at birth identified as female, 96% engaged in cross-dressing, 44% received psychotherapy, 24% underwent hormone therapy, and 14% had gender reassignment surgery. Mental health assessment revealed 78% had depression (ranging from mild to severe), 72% experienced moderate to severe anxiety, and 40% reported suicide attempts. Conclusions: Gender dysphoria patients in Bangladesh demonstrate a significant mental health burden with high rates of depression, anxiety, and suicidal behavior. Early recognition and timely multidisciplinary care, with psychotherapy and psychosocial support at its core, are essential to address mental health needs in this vulnerable population. [J Assoc Clin Endocrinol Diabetol Bangladesh, July 2026; 5 (2): e88864]